2016
DOI: 10.3148/cjdpr-2015-030
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Reliability Testing of NAK-50+: A Nutrition Attitude and Knowledge Questionnaire for Adults 50+ Years of Age

Abstract: NAK-50+ is a face valid and reliable questionnaire that assesses nutrition knowledge and attitudes in independent adults aged ≥50 years. Further work to determine construct validity and to refine the questionnaire is warranted. Availability of the questionnaire for this age group will support rigorous evaluation of education and self-management interventions for this segment of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Two negative kappa values were observed for responses to one nominal, select-all-that-apply type question. These type of questions received the lowest kappa scores in our study, and have also been found to perform worst and receive negative kappa values in other studies we reviewed [37,38].…”
Section: Discussionmentioning
confidence: 41%
“…Two negative kappa values were observed for responses to one nominal, select-all-that-apply type question. These type of questions received the lowest kappa scores in our study, and have also been found to perform worst and receive negative kappa values in other studies we reviewed [37,38].…”
Section: Discussionmentioning
confidence: 41%
“…The number of factors retained was determined by multiple criteria: Kaiser's eigenvalue, scree test, parallel analysis and Velicer's minimum average partial (MAP) test (Boateng et al, 2018). The reliability of the retained factors were computed as Cronbach α and their relatedness as corrected item to total correlations (ITC), values ≥ 0.70 and ≥ 0.2, respectively, were considered satisfactory (Ducak and Keller, 2016;Boateng et al, 2018;Taber, 2018).…”
Section: Study 3 -Pilot Testmentioning
confidence: 99%
“…Nutrition Knowledge: Participants completed the Nutrition Attitude and Knowledge Questionnaire for Adults 50+ Years of Age (NAK-50+) [13], on a tablet (iPad, Apple, Cupertino, USA) using an online survey (SurveyMonkey, San Mateo, USA). The NAK-50+ is comprised of 27 items on general nutrition knowledge and attitudes (e.g., healthy weight, exercise, appetite, food groups, fluids as well as meal replacements and food enjoyment).…”
Section: Five Times Sit To Stand (Ftss)mentioning
confidence: 99%